Zrównanie wieku emerytalnego w Polsce a kwestie równouprawnienia kobiet i mężczyzn na rynku pracy - ANDRUSZKIEWICZ, Iwetta (Przegląd Politologiczny, 2018)
The paper presents the solutions applying to retirement in Poland that combine two systems: the capitalization system and repartition. Trying to answer the question of whether different retirement ages for men and women is discriminatory, the author refers to the adjudi- cation of the Supreme Court and public opinion. The paper also indicates that the practice of giving notice of employment termination to women with permanent employment contracts only because they have acquired the right to retirement benefit violates the Constitution of Poland.